"We could think of things that could be science": Girls' re‐figuring of science in an out‐of‐school‐time club. Issue 9 (4th September 2013) - Gonsalves, Allison; Rahm, Jrène; Carvalho, Alice
Abstract Grounded in sociocultural theory, this study explores how the figured world of science is reworked through a series of multi‐media activities that were introduced into a girls‐only conversation club in an after school program for Teens. The study is part of a multi‐sited ethnography in which we explored youths' engagement with science within three sites. In this paper, we focus on a qualitative case study of one site. We present an analysis of the kinds of resources and cultural models of science that youth mobilized as they re‐figured science together over time, and in a space usually reserved for talk about girls' issues. Our study revealed that a meaningful introduction of science into an out‐of‐school‐time (OST) space that values youths' prior experiences seemed to depend on a two‐way exchange: re‐figuring their experiences as science‐experiences; and the re‐figuring of science to include their every‐day experiences. The study was successful in helping the girls re‐figure the world of science in ways that went beyond the mobilization of cultural models tied to school science only. Through collage, video production, formal and informal dialogue, youth mobilized resources from youth culture to position themselves as insiders to science and to refigure science to include resources from their everyday experiences. Yet, that figuring was also heavily marked by time and space. Follow‐up interviews point to a limited shifting of what counts as "real science" or how the youth consider themselves in relation to science. We conclude with a discussion of the gap between youth interest driven science experiences and science experiences driven by disciplinary practices detached from the world of youth. We discuss the implications of such a tension for introducing science into OST settings with program goals that extend beyond science learning. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 1068–1097, 2013